REGULATION AND SUPERVISION SHADOW BANKING INSTITUTIONS WHICH IS POTENTIALLY GIVES SYSTEMIC RISK AS AN EFFORT TO GIVE LAW PROTECTION TO CONSUMERS (Study in Banyumas Ex-Residency) - Dr. Sulistyandari S.H., M.Hum (Faculty of Law, Universitas Jenderal Soedirman, 2016)
Shadow banking practice there is a tendency to increase, then the regulator should be set. Some cases have led to financial stability system disorders and cause systemic risk. This study aims to reveal weaknesses in the regulation and implementation of shadow banking institutions that have the potential for systemic risk and the protection of customers both normative and implementation in the Ex-residency of Banyumas. This study is a qualitative study with normative juridical approach and the study of law as the law in action, a social science studies that non-doctrinal and empirical. The results showed that the implementation of the supervision of shadow banking in the former residency of Banyumas potential harm to customers primarily in LJKNB shaped KSP / KJKS that provide services to non members, LJKNB who misuse their permissions business activities, LJKNB that has not been incorporated, but no potential systemic. Factors law, law enforcement, facilities, people and culture affect the implementation of surveillance in the area of Ex-residency of Banyumas.Keywords: regulation, supervision, shadow banking